Folate titanium (IV)-chitosan nanocomposites as drug delivery system for active-targeted cancer therapy: Design, HSA/GSH binding, mechanistic, and biological investigations - Alsaed, Amera; Elshami, Fawzya I.; Ibrahim, Mohemed M.; Shereef, Hadeer; Mohany, Hany; van Eldik, Rudi; Shaban, Shaban Y. (Journal of Drug Delivery Science and Technology, 2024)
Folate Ti(IV)-chitosan nanocomposite (TiFA@CS NPs) were prepared from folate Ti(IV)-complex (TiFA) and chitosan (CS) with optimum particle size (175 ± 7 nm), high stability (ζ = −25.1 mV), and minimum hemolytic activity to target cells expressing folate receptors. The interaction with Human Serum Albumin (HSA), a target biomolecule, thought to be the primary pharmacological target of anticancer drugs, and Glutathione (GSH) considering that cisplatin resistance could be due to a reaction between cisplatin and GSH, were evaluated and revealed that, although TiFA@CS NPs show strong binding to HSA, compared to TiFA and FA, the former showed weaker binding to GSH and hence exhibits a lower resistant factor. Kinetic stability, affinity, and association constants of compounds-HSA were examined using a stopped-flow method, and the results show that the formulation of TiFA in TiFA@CS NPs alters the binding mechanism while also enhancing the coordination affinity and kinetic stability. Furthermore, in-vitro cytotoxicity revealed that active-targeting TiFA@CS NPs significantly inhibited FR-positive MCF-7 cells compared to FRs-negative A549 cells which in agreement with the binding constants and resistant factor. Moreover, in-vitro TiFA release assays using TiFA@CS NPs in 10 mM GSH, mimicking the tumor microenvironment, revealed increased TiFA release behavior. Together with its coordination affinity, release evaluations, and cytoxicity, TiFA@CS NPs showed good cell death and rapid tumor uptake, making them an excellent alternative for targeted drug delivery by FR.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Biocompatibility; Folate receptors; Nanomedicine; Targetted drugs; Titanium folate